Effect of standardized ileal digestible lysine level on growth performance of nursery pigs from 15 to 25 lb - J E Nemechek; J Usry; Michael D Tokach; Robert D Goodband; Joel M DeRouchey; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2010)
A total of 294 nursery pigs (PIC TR4 x 1050, initially 14.9 lb and 3 d postweaning) were used in a 28-d growth trial to evaluate the effects of standardized ileal digestible (SID) lysine level on pig growth performance. Pigs were allotted to 1 of 6 dietary treatments. There were 7 pigs per pen and 7 pens per treatment. Pigs and feeders were weighed on d 0, 7, 14, 21, and 28 to calculate ADG, ADFI, and F/G. A 2-phase diet series was used, with treatment diets fed from d 0 to 14 and a common diet fed from d 14 to 28. All diets were in meal form. The 6 SID lysine levels were 1.15, 1.23, 1.30, 1.38, 1.45, and 1.53%. From d 0 to 14, ADG and ADFI increased (quadratic; P<0.002) as SID lysine level increased from 1.15 to 1.30% where it began to plateau with no additional benefit observed from the three highest dietary lysine levels. Feed efficiency also improved (linear; P<0.0001) with increasing dietary lysine. From d 14 to 28, when the common diet was fed, there were no differences (P>0.36) in ADG, ADFI, or F/G. For the overall trial (d 0 to 28), the greatest improvement (quadratic; P<0.05) in ADG and ADFI was observed in pigs fed 1.30% SID lysine from d 0 to14; however, there was no difference (P>0.11) in overall F/G. In conclusion, the SID lysine requirement of 15- to 25-lb pigs was 1.30% or 3.86 g lysine/Mcal ME.; Swine Day, Manhattan, KS, November 18, 2010
Keywords: Swine Day; 2010; Kansas Agricultural Experiment Station contribution; no. 11-016-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1038; Lysine; Amino acid requirements; Nursery pig; Swine